Giat Interprofessional Collaboration Tenaga Kesehatan Tentang Peningkatan Kesadaran Masyarakat tentang Pentingnya Kontrol Kolesterol di Desa Tergo Kudus - Heni Setyoningsih; Gendis Purno Yudanti; Hasty Marta Wijaya; Dian Arsanti Palupi; Dwi Susiloningrum (Universitas Muria Kudus, 2026)
Cholesterol is a type of lipid essential for maintaining a healthy body, provided it remains within the optimal range. High cholesterol is prevalent among the elderly, as aging factors often lead to decreased physical activity, which in turn contributes to elevated cholesterol levels. Excessive cholesterol can accumulate in the arteries, necessitating dietary modifications and increased physical activity to prevent complications. High cholesterol levels significantly increase the risk of cardiovascular diseases and stroke. The purpose of this community service program is to enhance public awareness regarding the importance of monitoring blood cholesterol levels. The methods employed included health education and medical screenings, specifically blood pressure and blood glucose/cholesterol tests, conducted during routine Integrated Healthcare Center (Posyandu) sessions for the elderly. The results of this program demonstrate that these activities successfully improved the understanding of the Tergo Village community concerning the importance of regular cholesterol control.